Ewing’s Sarcoma of the Lung as a Second Malignancy in Long-Term Survivor of Childhood Hodgkin’s Lymphoma: A Rare Case Report and Literature Review - Sumit Bharti; Deepak Bhasin; Gautam Goyal; Priya Sharma (European Medical Journal Oncology)
In patients with haematologic malignancies such as lymphoma and leukaemia, significant increases in survival have been seen, due to advances in treatment strategies. However, long-term survivors of these cancers still remain at a higher risk of developing second cancers during their lifetime, especially in the fourth decade. It is well known that immunodeficiency after radiotherapy, chemotherapy, or haematopoietic stem cell transplantation impairs the antitumour activity of the innate and adaptive immune systems, predisposing the immune system to fail to detect and eliminate newly mutated cells. Literature shows evidence of various malignancies in these survivors, including sarcomas; breast cancers; mesothelioma; and solid secondary malignancies like breast cancer, thyroid cancer, and bone or soft tissue sarcoma. Here, the author reports a case of development of Ewing’s sarcoma of the lung in an adult who is a long-term survivor of Hodgkin’s lymphoma.